INTERNALISASI NILAI ETIKA LINGKUNGAN DI SEKOLAH DASAR - Mardiana, Dinny (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
The research background  was environmental education in school had not reach affection domain, which should be embedding environmetal ethics. The research was using qualitative approach. The results of research showed that: the Internalization of Environmental Ethics Value process in school was occured through ten ways which  resulted  nine stages of student’s responses as a mechanism.